GE_GERICHTE C/25977/2008 vom 8. November 2013 - GE Cour de justice (2013)
; BANQUE ; CRÉDIT HYPOTHÉCAIRE ; RÉSILIATION ANTICIPÉE ; INDEMNITÉ(EN GÉNÉRAL) ; CLAUSE PÉNALE | CO.160 CO.161 CO.162 CO.163 CO.312 CC.2.2